COMMUNITY SERVICE TO PREGNANT WOMEN IN COMPLIANCE WITH CONSUMING FE TABLETS IN LADANG BAMBU VILLAGE, MEDAN TUNTUNGAN DISTRICT - Rizky Andriana Bakara; Arva Rochmawati (Cattleya Darmaya Fortuna, 2024)
Anemia in pregnant women is still a major health problem that is at risk of causing complications of childbirth and low birth weight (BBLR). One of the factors causing it is the low compliance of pregnant women in consuming Fe (Blood Supplement) tablets. This community service activity aims to increase the knowledge and compliance of pregnant women in consuming Fe tablets through structured education. The program was held on March 29, 2024 in Ladang Bambu Village, Medan Tuntungan District, with interactive counseling methods, demonstrations of correct consumption methods, and group discussions. The results of the evaluation showed a significant increase in participants' knowledge of the importance of iron for fetal health as well as an improvement in attitudes in maintaining discipline in consuming Fe tablets. This education is expected to be able to reduce the prevalence of anemia in the work area of Ladang Bambu Village and support the health of the mother and fetus optimally.